Elite international female rugby union physical match demands: A five-year longitudinal analysis by position and opposition quality - Mark Waldron (Journal of Science and Medicine in Sport, 2021)
ObjectivesThis study aimed to evaluate changes in rugby union physical match characteristics across five seasons of International female competition, according to position and opposition quality.Design & methodsGlobal positional systems and performance analysis data from 78 female rugby union players (minimum of five international appearances) were analysed between 2015 and 2019. Mixed-linear-modelling was used to investigate the effects of season, opposition and position during 969 individual match performances from 53 International matches.ResultsRunning demands increased between 2015 and 2017 (World Cup year) and plateaued thereafter, except for sprints among the outside backs, which declined between 2017 and 2019, and accelerations and decelerations >3 m s2 which increased between 2017 and 2019. Collisions were higher in forwards than backs, and highest against stronger opposition. Running demands were greater against weaker opposition, but the ‘most intense periods’ of running were greater against stronger opposition in 2017.ConclusionsMatch demands increased between 2015 and the 2017 World Cup year, which was underpinned by increased sprinting and greater running during maximum intensity periods against top 5 opposition. The increase in accelerations and decelerations in the latter years, alongside the maintenance of average running demands and collision counts, is consistent with the reported continuous playing style of female rugby, thus placing specific demands on players and requiring tailored training methods. Some positions (Forwards and Scrum-halves) appear to be important for this adopted style, demonstrating concomitantly high relative collision and running intensities.